Cyanobacterial carbon metabolism: Fluxome plasticity and oxygen dependence. Issue 7 (30th March 2017) - Wan, Ni; DeLorenzo, Drew M.; He, Lian; You, Le; Immethun, Cheryl M.; Wang, George; Baidoo, Edward E. K.; Hollinshead, Whitney; Keasling, Jay D.; Moon, Tae Seok; Tang, Yinjie J.
ABSTRACT: Synechocystis sp. strain PCC 6803 has been widely used as a photo‐biorefinery chassis. Based on its genome annotation, this species contains a complete TCA cycle, an Embden‐Meyerhof‐Parnas pathway (EMPP), an oxidative pentose phosphate pathway (OPPP), and an Entner–Doudoroff pathway (EDP). To evaluate how Synechocystis 6803 catabolizes glucose under heterotrophic conditions, we performed 13 C metabolic flux analysis, metabolite pool size analysis, gene knockouts, and heterologous expressions. The results revealed a cyclic mode of flux through the OPPP. Small, but non‐zero, fluxes were observed through the TCA cycle and the malic shunt. Independent knockouts of 6‐phosphogluconate dehydrogenase ( gnd ) and malic enzyme ( me ) corroborated these results, as neither mutant could grow under dark heterotrophic conditions. Our data also indicate that Synechocystis 6803 metabolism relies upon oxidative phosphorylation to generate ATP from NADPH under dark or insufficient light conditions. The pool sizes of intermediates in the TCA cycle, particularly acetyl‐CoA, were found to be several fold lower in Synechocystis 6803 (compared to E. coli metabolite pool sizes), while its sugar phosphate intermediates were several‐fold higher. Moreover, negligible flux was detected through the native, or heterologous, EDP in the wild type or Δ gnd strains under heterotrophic conditions. Comparing photoautotrophic, photomixotrophic, and heterotrophic conditions, the Calvin cycle, OPPP, and EMPP in Synechocystis 6803 possess the ability to regulate their fluxes under various growth conditions (plastic), whereas its TCA cycle always maintains at low levels (rigid). This work also demonstrates how genetic profiles do not always reflect actual metabolic flux through native or heterologous pathways. Biotechnol. Bioeng. 2017;114: 1593–1602. © 2017 Wiley Periodicals, Inc. Abstract : Phototrophic and heterotrophic metabolisms in Synechocystis 6803 were studied using flux/metabolite analyses, genome scale modeling, gene knockouts, and heterologous expressions. Cyanobacterial sugar phosphate pathways demonstrate flexible flux organizations under various growth conditions (plastic), whereas its TCA cycle always maintains at low levels (rigid). Thereby, Synthetic Biology efforts should focus on sugar phosphate intermediates to deliver fluxes toward bio‐productions.